Fabrication and Characterisation of Magnetorheological Shear Thickening Fluids - Sokolovski, Vladimir; Tian, Tongfei; Ding, Jie; Li, Weihua (Frontiers in Materials, 2020)
In this article, a magnetorheological shear thickening fluid (MRSTF) was fabricated based on magnetorheological (MR) material and shear thickening fluid (STF). The STF was firstly fabricated as the liquid phase, and carbonyl iron particles were then mixed with the prefabricated STF to synthesise a series of MRSTFs with various iron concentrations. Then, a rheometer was used to measure their viscosities by varying the shear rate under various magnetic fields. Both static and dynamic tests were conducted to study the rheology of MRSTFs under different magnetic fields. The tested results revealed that the MRSTF showed shear thickening under zero magnetic field and MR effect with increasing applied magnetic field. It was also noted that the viscosity of the MRSTFs can be controlled by both shear rate and the applied magnetic field. The concentration of iron particles played an important role in the MRSTFs’ rheological properties. The MRSTFs with higher iron particle concentrations revealed lower shear thickening effects but higher MR effects, which means the MRSTF with higher iron concentration can be treated as an effective MR fluid. Meanwhile, the MRSTF with low iron concentration displays good shear thickening effect under weak magnetic field. To summarise the behavior of MRSTFs with various iron concentrations and under different magnetic fields, three regions were proposed to provide guidelines to design MRSTFs and assist in their applications.